Reactive and neoplastic lymphocytes in human bone marrow: morphological, immunohistological, and molecular biological investigations on biopsy specimens. - Kröber, S M (1999)
BACKGROUND: Slight, diffuse or focal lymphocyte proliferation is relatively common in bone marrow biopsy specimens. It may be impossible to determine whether this represents a reactive lymphocytosis or low grade non-Hodgkin lymphoma (NHL) on the basis of routine investigations alone. AIM: To investigate the supplementary use of molecular biological techniques in this situation. METHODS: 529 formalin fixed, paraffin embedded bone marrow biopsy specimens from the iliac crest were subjected to histological and immunohistochemical staining to determine the number and nature of the lymphocytes present. The cases were divided into three groups according to the lymphocyte count: normal (< 10% of nucleated bone marrow cells), slightly increased (10-30%), and markedly increased (> 30%). All of the last group could be diagnosed as NHL from the morphological findings alone. The clonality of rearrangements of the IgH and TCR gamma genes was investigated by polymerase chain reaction (PCR). RESULTS: Monoclonality was observed in 7.5% of the 372 cases with a normal lymphocyte count, in 50% of the cases with a modest increase in lymphocyte numbers (suggesting a diagnosis of low grade NHL not detected by immunostaining), and in 77% of the cases with markedly increased lymphocyte numbers. CONCLUSIONS: If PCR is used in addition to the immunohistochemical investigation of bone marrow biopsies, considerably more cases of NHL can be identified, making this of particular use in staging and detection of recurrences.